Parent–infant psychotherapy: a systematic review of the evidence for improving parental and infant mental health. (19th October 2016) - Barlow, Jane; Bennett, Cathy; Midgley, Nick; Larkin, Soili K.; Wei, Yinghui
Abstract: Background: Parent–infant psychotherapy (PIP) is a psychodynamic intervention with parent–infant dyads, designed to address regulatory disturbances in infancy and problems in the parent–infant relationship. Aims: This systematic review aimed to examine whether PIP is effective in improving the parent–infant relationship or other aspects of parent or infant functioning. Methods: A systematic review was undertaken. Electronic databases were searched for randomised controlled trials in which participants had been allocated to a PIP intervention or control group/other treatment. Results: Eight studies were identified that provided data comparing parent–infant psychotherapy with a no-treatment control group (four studies) or comparing PIP with other kinds of treatment (four studies). Meta-analyses indicated that parents who received PIP were more likely to have an infant who was rated as being securely attached to the parent after the intervention; however, there were no significant differences in studies comparing outcomes of PIP with another model of treatment. Conclusions: Although PIP appears to be a promising method of improving infant attachment security, there is inconclusive evidence of its benefits in terms of other outcomes, and no evidence to show that it is more effective than other interventions for parents and infants. Many studies had limitations in their design or implementation, and findings must be interpreted with caution.